Low Pressure Strand Burner for Solid Propellant Burning Rate Studies - Amir, Aziz; R., Mamat; W. K., Wan Ali (2013)
It is well-known that a strand burner is an apparatus that provides burning rate measurements of a solid propellant at an elevated pressure in order to obtain the burning characteristics of a propellant. The objective of this paper is to describe the facilities developed by author that was used in the author’s studies. The low pressure strand burner has a mounting stand that allows the propellant strand to be mounted vertically. The strand was ignited electrically using hot wire, and the burning time was recorded by electronic timer. Wire technique was used to measure the burning rate. The burning rate characteristics of solid propellant have be evaluated over five different chamber pressures ranging from 1 atm to 31 atm. Preliminary results from these techniques are presented. This study shows that the strand burner can be used on propellant strands to obtain accurate low pressure burning rate data.